2017
DOI: 10.1177/1535370217736512
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis identifies differentially regulated networks between osteosarcoma and normal bone samples

Abstract: We performed whole transcriptome analysis of osteosarcoma bone samples. Initially, we sequenced total RNA from 36 fresh-frozen samples (18 tumoral bone samples and 18 non-tumoral paired samples) matching in pairs for each osteosarcoma patient. We also performed independent gene expression analysis of formalin-fixed paraffin-embedded samples to verify the RNAseq results. Formalin-fixed paraffin-embedded samples allowed us to analyze the effect of chemotherapy. Data were analyzed with DESeq2, edgeR and Reactome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 39 publications
2
70
0
Order By: Relevance
“…For instance, Jeon et al [ 23 ] found that knockdown of ACACB could compensate for AMPK activation and facilitate anchorage-independent growth and solid tumor formation in vivo , whereas the activation of ACACB could attenuate these processes. Ho et al [ 24 ] observed that the expression level of ACACB was significantly different between osteosarcoma and normal bone samples. The above findings suggested that ACACB might be a novel gene associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jeon et al [ 23 ] found that knockdown of ACACB could compensate for AMPK activation and facilitate anchorage-independent growth and solid tumor formation in vivo , whereas the activation of ACACB could attenuate these processes. Ho et al [ 24 ] observed that the expression level of ACACB was significantly different between osteosarcoma and normal bone samples. The above findings suggested that ACACB might be a novel gene associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the functional role of MT1-MMP in osteosarcoma has not been experimentally addressed, but expression studies clearly suggest an involvement in the progression of this disease. We have previously demonstrated the expression of MT1-MMP on the tumor cells in human osteosarcoma specimens using IHC 14 and in a transcriptome analysis of human osteosarcoma samples, MT1-MMP was found to be among the 10 most upregulated genes 24 . Furthermore, high MT1-MMP expression levels are correlated with poor survival in osteosarcoma patients 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously published gene counts from fresh-frozen tumor were downloaded from Gene Expression Omnibus (GEO) under accession No. GSE99671 [9]. For the cell lines, raw FASTQ files were downloaded from GSE118488 [10].…”
Section: Methodsmentioning
confidence: 99%